Peranan Sarak Opat dalam Masyarakat Gayo - Darmawan Darmawan (Universitas Syiah Kuala, 2010)
ABSTRACT: The structure of Sarak Opat in Gayo community is still implemented strongly, and if occur dispute among community in Gayo is always settled through this traditional institution. Most of customary provisions which still remain exist even though overlap with national written law. Sarak Opat institution is still exist, nevertheless the community and national law advance causes Sarak Opat Institution occurring deviation concept from the pure value. The Roles of Sarak Opat in Gayo Community